Rapid growth and catastrophic destruction events of Planchón Volcano, Southern Andes - José Antonio Naranjo; Jorge Romero; Juan Pablo Contreras; Yuji Orihashi; Kevin Scott; Miguel Haller; Hirochika Sumino (Volcanica, 2024)
During the Late Pleistocene-to-Holocene, the mafic Planchón volcano (35.2 °S, Southern Andes) experienced two important destructive events: a sector collapse to the west and a multiphase explosive eruption transforming the east summit area. We provide new field and laboratory evidence, including geochemical, geochronologic, and geological-morphological analysis, to reconstruct the evolution, triggering mechanisms, and physical parameters of these events.The lateral collapse (48~ka BP) was mainly predisposed by a tectonically westward-inclined substratum and rapid edifice growth rates (0.3–0.48 km3 ka-1). The resulting Planchón-Teno debris avalanche became valley-confined traveling at c. 260 km h-1 up to 95 km distance and forming an 8.6 ± 1.3 km3 deposit. The resulting 4.1 km wide amphitheater was later destroyed at c. 7 ka BP by the multiphase Valenzuela phreatomagmatic eruptions, forming a c. 2.5 km diameter caldera. The case of the Planchón volcano warns that rapidly growing mafic volcanoes imply a substantial catastrophic hazard increase for the surrounding areas.